Mudharabah Hasil Pertanian Di Tinjau Dari Undang Undang Dan Hukum Islam - Jannahar Saddam Ash Shidiqie (JESI (Jurnal Ekonomi Syariah Indonesia), 2017)
This research aims to analyze the implementation of profit sharing agreement for paddy field in Gamping Sub-district using Law No. 2 of 1960 and Islamic Law. The conclusion of this study are: The implementation of profit sharing agreement for paddy fields in Gamping Sub-district is not fully in accordance with the Law No. 2 of 1960 and the Islamic law. The agreement of profit sharing in Gamping Sub-district in general is conducted orally, based on trust, and without any witnesses. The balance of profit sharing used in general is "maro" (½ part for sharecroppers and ½ part for owner) with all the production costs borne by the sharecroppers. In the event of crop failure, it becomes the risk borne by the sharecroppers. The crop yields reaching specific nisab or limit in general are not directly paid for the zakat. The obstacles to implement the Law No. 2 of 1960 and the Islamic Law in Gamping Sub-district are because there is no socialization from any parties related to Law No. 2 of 1960 and the Islamic Law in agricultural cooperation, here is hereditary habit, the owners and sharecroppers do not want to use complicated procedure, the owners have been good enough and fair with the common system used, and the sharecroppers accept the habit in force although they feel that it is hard and unfair. The bargaining position between the owner and sharecroppers at Gamping Sub-district is devided into three phases: in the past, the number of sharecroppers was more than the number of owner; currently, the number of sharecroppers is declining; and in the future, the sharecroppers  will be lesser than the number of owner so these will increase  the bargaining position of the sharecroppers (it is the answer to implement Law No.2 of 1960 and Islamic Law.